Tourist Perceptions of Climate Change Impacts on Mountain Ecotourism in Southern Mexico - Ginger Deason; Erin Seekamp; Adam Terando; Camila Rojas (Tourism and Hospitality, 2023)
Climate change impacts on tourism are well documented, with most studies focusing on challenges facing ski or beach tourism. While non-ski, mountain tourism accounts for almost one fifth of tourism worldwide, there is a dearth of research on tourists’ perceptions of climate change impacts and their effects on tourism demand in these areas. This study, conducted at the ecotourism destination of the Pueblos Mancomunados in the Sierra Norte Mountains of southern Mexico, helps to fill that gap by identifying important tourist decision factors and determining how tourists’ decisions to visit may change under different climatic conditions. Using on-site intercept survey research methodology involving 188 tourists, we found that some climate change scenarios affect tourists’ perceptions of the desirability of visiting nature-based tourism sites. Results indicate that community-based ecotourism businesses, such as the one that operates in the Pueblos Mancomunados, need to specifically plan for climate change impacts, as they may need to alter tourism offerings to sustain demand.